Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1007/s007050170018
|View full text |Cite
|
Sign up to set email alerts
|

The genome segment B encoding the RNA-dependent RNA polymerase protein VP1 of very virulent infectious bursal disease virus (IBDV) is phylogenetically distinct from that of all other IBDV strains

Abstract: A full-length cDNA clone of the segment B of the very virulent infectious bursal disease virus (IBDV) strain BD 3/99 was constructed and the full-length nucleotide sequence was established. The nucleotide sequence encoding VP1, an RNA-dependent RNA polymerase, of BD 3/99 was aligned with that of 17 other IBDV strains including six very virulent, three classical virulent, five classical attenuated, one antigenic variant and two serotype 2 strains. The VP1 genes of all very virulent strains were 97.5% to 99.8% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 36 publications
7
29
1
Order By: Relevance
“…In contrast, in the BMCMC phylogeny of VP1, the vvIBDV clade (vvVP1) was excluded from the lineage containing all other serotype I and II IBDV strains (0.87 BP support) (Fig. 1B), revealing an independent phylogenetic origin of vvVP1 that agreed with previous reports (17). The high BP support (0.99) of the monophyletic IBDV VP1 lineage in the birnavirus VP1 phylogeny suggests that vvVP1 may have an avian origin that shares the TMRCA with the other IBDV strains.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, in the BMCMC phylogeny of VP1, the vvIBDV clade (vvVP1) was excluded from the lineage containing all other serotype I and II IBDV strains (0.87 BP support) (Fig. 1B), revealing an independent phylogenetic origin of vvVP1 that agreed with previous reports (17). The high BP support (0.99) of the monophyletic IBDV VP1 lineage in the birnavirus VP1 phylogeny suggests that vvVP1 may have an avian origin that shares the TMRCA with the other IBDV strains.…”
Section: Resultssupporting
confidence: 90%
“…Phylogenetic analyses have revealed independent evolutionary histories of the two genome segments (17,44), suggesting that a reassortment event may have played a role in the emergence of vvIBDV. Previous reports suggested that both the major capsid protein (VP2) and the RNA-dependent RNA polymerase (VP1), which are located on genome segments A and B, respectively, contribute to the virulence of IBDV (1-3, 26, 43).…”
Section: Infectious Bursal Disease Virus (Ibdv) Is a Birnavirus Causimentioning
confidence: 99%
“…VP2 is, however, unlikely to be the only factor for virulence: laboratory-engineered reassortant viruses derived from vvIBDV exhibited delayed replication in the bursa (37) or failed to induce morbidity and mortality (31) unless they also had a typical vvIBDV-related segment B. This observation is consistent with the phylogeny-based hypothesis that both genome segments may be involved in the emergence of vvIBDV (38,39). Recently, this hypothesis was substantiated by the isolation of three naturally occurring segment B-reassorted vvIBDV isolates, all with reduced pathogenicity in chickens (40,41).…”
Section: Nfectious Bursal Disease Virus (Ibdv) Of Chickens (Gallus supporting
confidence: 58%
“…Changes in the variable region of VP2 should be considered evolutionary rather than virulence markers and the potential for new and antigenically divergent lineages of vvIBDVs in the future should not be excluded. Sequence comparisons between pathogenic and non-pathogenic serotype 1 strains have shown differences throughout the genome (Brown & Skinner, 1996;Yamaguchi et al, 1997;Pitcovski et al, 1998;Yehuda et al, 1999;Islam et al, 2001) indicating that different areas of the genome might contribute to virulence. In order to investigate this further, full-length sequencing and comparison of the genomes of the nine investigated strains is in progress.…”
Section: Discussionmentioning
confidence: 99%